Biodegradability Kraft Paper Coated with Films Emulsified Chitosan and Palmitic Acid - Reis, Arlete B.; Yoshida, Cristiana M.P.; Vilela, Elke S.D.; Nascimento, Rosely S.; Melo, Itamar S.; Franco, Telma T. (Journal of Research Updates in Polymer Science, 2013)
The use of natural polymers is an alternative to polymers derived from petroleum that may reduce industrial waste and contribute to the environmental protection. Following the same reasoning, the biodegradability of paper packaging is already known for it being a product originated from cellulosic materials (cellulosic fibers). The aim of this work was to assess the process of degradation from the junction of two different materials; biopolymer and sheets of paper. This paper proposes the study of the biodegradability of chitosan film-coated Kraft paper sheets and emulsified chitosan film-coated Kraft paper sheets added with palmitic acid, both in comparison with uncoated Kraft paper sheets. The biodegradability study was conducted based on analyses of biofilm formation by Scanning Electron Microscopy (SEM), soil respiration, Gravimetry, Microbial Biomass Carbon and enzymatic soil activity and evaluation.